Mediasi Kepuasan Pengunjung Dalam Mempengaruhi Nilai Pelanggan Dan Kualitas Pelayanan Serta Dampaknya Terhadap Loyalitas Pengunjung (Studi Pada Pengunjung Edu Wisata Lontar Sewu Desa Hendrosari Kabupaten Gresik) - Maulidyah, Intan; Suyono, Suyono (Management Department of Economics and Business Of Trunojoyo Madura University, 2024)
This study aims to determine the effect of customer value and service quality through visitor satisfaction and its impact on visitor loyalty. The method used in this study was purposive sampling, namely the sampling technique by considering certain criteria with a total sample of 96 respondents. With the method of multiple linear regression analysis and path analysis.The results of this study indicate that Customer value has a positive and significant effect on visitor satisfaction at Hendrosari Lontar Sewu Tourism Edu; The quality of service has a positive and significant effect on visitor satisfaction at the Lontar Sewu Hendrosari Educational Tour; Customer value has a negative and insignificant effect on isitor loyalty at Lontar Sewu Hendrosari Tourism Edu; Customer quality has a positive and significant effect on visitor loyalty at Lontar Sewu Hendrosari Tourism Education; Visitor satisfaction has a positive and significant effect on visitor loyalty at Hendrosari Lontar Sewu Tourism Edu. Customer value has a positive and significant effect on visitor loyalty through visitor satisfaction at Hendrosari Lontar Sewu Tourism Edu. 7) Service quality has a positive and significant effect on visitor loyalty through visitor satisfaction at Hendrosari Lontar Sewu Tourism Edu.